2019
DOI: 10.1007/s40266-019-00661-0
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Topical Non-steroidal Anti-Inflammatory Drugs in Osteoarthritis: Outcomes of a Systematic Review and Meta-Analysis

Abstract: Objective We aimed to assess the safety of topical non-steroidal anti-inflammatory drugs (NSAIDs) in the management of osteoarthritis (OA) in a systematic review and meta-analysis of randomized, placebo-controlled trials. Methods A comprehensive literature search was undertaken in the MEDLINE, Cochrane Central Register of Controlled Trials (CENTRAL), and Scopus electronic databases. Randomized, double-blind, placebo-controlled, parallel-group trials that assessed advers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 47 publications
0
44
0
6
Order By: Relevance
“…Topical NSAIDs may be added to the treatment regimen in Step 1 therapy if the patient is still symptomatic, and may be used in preference to oral NSAIDs particularly in patients aged ≥ 75 years as they have similar efficacy to the oral medications in reducing pain (ES 0.44, 95% CI 0.27, 0.62) with a reduced risk of systemic AEs [4]. An increase in mild local skin reactions is observed with topical NSAIDs although this may be product-specific, and is notably higher with diclofenac [17]. Topical NSAIDs are recommended as add-on analgesia in Step 1 for patients who are still symptomatic, and prior to the use of oral NSAIDs [4].…”
Section: Nsaidsmentioning
confidence: 99%
“…Topical NSAIDs may be added to the treatment regimen in Step 1 therapy if the patient is still symptomatic, and may be used in preference to oral NSAIDs particularly in patients aged ≥ 75 years as they have similar efficacy to the oral medications in reducing pain (ES 0.44, 95% CI 0.27, 0.62) with a reduced risk of systemic AEs [4]. An increase in mild local skin reactions is observed with topical NSAIDs although this may be product-specific, and is notably higher with diclofenac [17]. Topical NSAIDs are recommended as add-on analgesia in Step 1 for patients who are still symptomatic, and prior to the use of oral NSAIDs [4].…”
Section: Nsaidsmentioning
confidence: 99%
“…Recently, the ESCEO commissioned several systematic reviews and meta-analyses of randomized, placebo-controlled trials to reassess the safety of various anti-OA medications, including topical nonsteroidal anti-inflammatory drugs (NSAIDs), symptomatic slow-acting drugs for OA (SYSADOAs) and intra-articular hyaluronic acid (IAHA) [30][31][32]. For this purpose, the MEDLINE, Cochrane Central Register of Controlled Trials, and Scopus databases were comprehensively searched.…”
Section: Methodsmentioning
confidence: 99%
“…The methodology and the outcomes of these systematic reviews have been extensively described in each manuscript. From the articles included in each systematic review, we collected information on how AE data were reported; details on how AE-related results were reported in each article retrieved from the systematic review processes can be found in the tables describing the characteristics of the included studies in each specific manuscript reporting the outcomes of these new meta-analyses (in this supplement) [30][31][32]. For the purpose of preparing the ESCEO recommendations for the reporting of harms in future manuscripts on trials on anti-OA medications, we summarized the ways in which harms-related data have been reported across the articles retrieved for these new ESCEO meta-analyses, and report here the common sub-standard harms reporting practices found in these prior manuscripts on RCTs on anti-OA drugs.…”
Section: Methodsmentioning
confidence: 99%
“…Adverse events associated with topical diclofenac are primarily local reactions at the application site (dry skin, redness/erythema, pruritus) with minimal systemic effects. A meta-analysis of topical NSAIDs found higher rates of overall adverse events (odds ratio [OR] 1.30; 95% CI 1.10-1.53) with topical diclofenac compared with placebo (N = 8 studies) in studies of knee or hand OA, driven predominantly by increased skin and subcutaneous tissue disorders (OR 1.73; 95% CI 0.96-3.10) [44]. However, there was no increase in gastrointestinal adverse events (OR 1.11; 95% CI 0.75-1.64) and no increase in severe events (OR 1.19; 95% CI 0.68-2.07) or serious events (OR 0.94; 95% CI 0.26-3.42) compared with placebo [44].…”
Section: Topical Diclofenac Safety and Tolerability In Osteoarthritismentioning
confidence: 99%
“…A meta-analysis of topical NSAIDs found higher rates of overall adverse events (odds ratio [OR] 1.30; 95% CI 1.10-1.53) with topical diclofenac compared with placebo (N = 8 studies) in studies of knee or hand OA, driven predominantly by increased skin and subcutaneous tissue disorders (OR 1.73; 95% CI 0.96-3.10) [44]. However, there was no increase in gastrointestinal adverse events (OR 1.11; 95% CI 0.75-1.64) and no increase in severe events (OR 1.19; 95% CI 0.68-2.07) or serious events (OR 0.94; 95% CI 0.26-3.42) compared with placebo [44]. Another meta-analysis reported no increase in systemic adverse events (RR 0.89; 95% CI 0.59-1.3) or gastrointestinal adverse events (RR 1.1; 95% CI 0.76-1.6) with topical diclofenac compared with carrier alone in knee and hand OA [30].…”
Section: Topical Diclofenac Safety and Tolerability In Osteoarthritismentioning
confidence: 99%